STRATEGI KEPOLISIAN RESORT BUTON UTARA DALAM MENINGKATKAN KEPERCAYAAN PUBLIK MELALUI PENERAPAN COMMUNITY POLICING - La Ode Hamin; Muhamad Askal Basir; Sri Mayunita (Halu Oleo University, 2025)
The declining public trust in the police institution poses a serious challenge to establishing a participatory and sustainable security system. This study aims to analyse the strategy of the North Buton Resort Police in strengthening public trust through the Community Policing approach. This research uses a qualitative method with a case study approach and SWOT analysis to explore the strengths, weaknesses, opportunities, and threats in the implementation of the strategy. The findings show that the strategy is carried out through dialogical patrols, community partnership forums, legal education, and the active presence of community-based police officers. This strategy has had a positive impact on increasing community participation in maintaining security and strengthening social relations between the police and the public. However, there are obstacles such as limited personnel, inadequate operational facilities, and geographical challenges that require systemic improvements and cross-sector collaboration. The conclusion of this study states that the success of the Community Policing strategy highly depends on the ability to adapt to the local social context, along with policy support and community engagement. These findings can serve as a reference for developing community-based security policies in other regions with similar social characteristics.